Seminal plasma microbiomes, sperm parameters, and cryopreservation in a healthy fertile population - Fu, Longlong; Lou, Yuanlei; Guo, Ying; Zhou, Fang; Ma, Jing; Wang, Shusong; Gu, Yiqun; Fu, Bin; Lu, Wenhong (Frontiers in Microbiology, 2024)
Background: Recent advances in microbiome research have revealed the presence of diverse microbial communities in human tissues previously thought to be sterile. The present study delves into the emerging field of seminal plasma microbiomics, examining the relationship between semen microbes and semen parameters and postfreezing tolerance.The study involved a cohort of healthy fertility males and microbial genome analysis using 16S rRNA to characterize the microbial diversity of seminal plasma.Microbial diversity analysis identified unique amplicon sequence variants (ASVs) and genera dominant in seminal plasma. Spearman's correlation coefficient was used to assess the relationship between flora and semen parameters. A paired t-test was used to compare the changes in microbiome expression in seminal plasma before and after cryo-resuscitation.The relevant results show that the top five phyla in terms of abundance of seminal plasma microbiome were Firmicutes, Bacteroidota, Proteobacteria, Actinobacteriota, and Campylobacterota. Spearman correlation analysis highlighted the association between specific microbial species and semen parameters, between Porphyromonas_asaccharolytica and sperm concentration. Microbial changed significantly after cryo-resuscitation, affecting taxonomic units such as Campylobacter and Muribaculaceae, and KEGG enrichment analyses, suggesting that metabolic pathways are associated with sperm freezing. Eubacterium_coprostanoligenes and Eptoniphilus_duerdenii exhibited a potential impact, whileOrynebacterium_tuberculostearicum demonstrated a positive correlation with the recovery rate of progressive motile sperm.The semen of normal fertile individuals contains a microflora component that is closely related to semen quality, including the sperm's ability to withstand freezing.